2018
DOI: 10.3390/molecules23071620
|View full text |Cite
|
Sign up to set email alerts
|

Chalcone Derivatives Enhance ATP-Binding Cassette Transporters A1 in Human THP-1 Macrophages

Abstract: Atherosclerosis is a process of imbalanced lipid metabolism in the vascular walls. The underlying pathology mainly involves the deposition of oxidized lipids in the endothelium and the accumulation of cholesterol in macrophages. Macrophages export excessive cholesterol (cholesterol efflux) through ATP-binding cassette transporter A1 (ABCA1) to counter the progression of atherosclerosis. We synthesized novel chalcone derivatives and assessed their effects and the underlying mechanisms on ABCA1 expression in mac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 61 publications
0
12
0
1
Order By: Relevance
“…Human gene MIR10B contains one unannotated SNP, rs1388274194, able to elevate the miR-10b level (Figure 2f), and another one, rs564940769, which can reduce it (Table 9). Next, a keyword search of PubMed [38] pointed to a biochemical research article [173] about an miR-10b deficit as an atheroprotector. That is why we recommend two candidate SNP markers (rs1388274194 and rs564940769) of speeding up and slowing down atherogenesis, respectively (Table 9).…”
Section: Looking Throughmentioning
confidence: 99%
“…Human gene MIR10B contains one unannotated SNP, rs1388274194, able to elevate the miR-10b level (Figure 2f), and another one, rs564940769, which can reduce it (Table 9). Next, a keyword search of PubMed [38] pointed to a biochemical research article [173] about an miR-10b deficit as an atheroprotector. That is why we recommend two candidate SNP markers (rs1388274194 and rs564940769) of speeding up and slowing down atherogenesis, respectively (Table 9).…”
Section: Looking Throughmentioning
confidence: 99%
“…We previously revealed that the chalcone derivative, 1m, enhances ABCA1 expression in THP‐1 macrophages (Teng et al, 2018). To develop a more potent and multifunctional molecule than 1m, we synthesized six chalcone derivatives: 1m ‐ 1 to 1m‐6 (Figures S1A and 1a).…”
Section: Resultsmentioning
confidence: 99%
“…Kelch-like ECH-associated protein 1 is a repressor protein that binds to Nrf2 and promotes its degradation. The conformation change of kelch-like ECH-associated protein 1 results in nuclear translocation of Nrf2 and subsequent target gene expression (Kansanen, Kuosmanen, Leinonen, & Levonen, 2013;Taguchi, Motohashi, & Yamamoto, 2011). Accordingly, the effects of 1m-6 on kelch-like ECH-associated protein 1 inhibition require further investigation in future studies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations